European Handbook of Neurological Management 2006
DOI: 10.1002/9780470753279.ch16
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one among the most frequent neurological disorders. Of all TBIs 90% are considered mild with an annual incidence of 100-300/100 000. Intracranial complications of mild traumatic brain injury (MTBI) are infrequent (10%), requiring neurosurgical intervention in a minority of cases (1%), but poten tially life threatening (case fatality rate 0.1%). Hence, a true health management problem exists because of the need to exclude the small chance of a life-threatening complication in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 91 publications
0
5
0
1
Order By: Relevance
“…18 Injury severity was categorized into mild TBI (GCS 15 to 13, loss of consciousness duration #30 minutes, posttraumatic amnesia duration #1 hour) without risk factors (mild RF-TBI, n = 24) or with $1 risk factor (mild RF+ TBI, n = 52) and moderate/severe TBI (GCS 12 to 3, loss of consciousness duration $30 minutes, posttraumatic amnesia duration $1 hour; n = 37). 19 …”
Section: Injury Severitymentioning
confidence: 99%
“…18 Injury severity was categorized into mild TBI (GCS 15 to 13, loss of consciousness duration #30 minutes, posttraumatic amnesia duration #1 hour) without risk factors (mild RF-TBI, n = 24) or with $1 risk factor (mild RF+ TBI, n = 52) and moderate/severe TBI (GCS 12 to 3, loss of consciousness duration $30 minutes, posttraumatic amnesia duration $1 hour; n = 37). 19 …”
Section: Injury Severitymentioning
confidence: 99%
“…Studies showed that handing out discharge information and scheduling routinely follow-up sessions could reduce these post-traumatic symptoms. 10,11 However, still little is known about the optimal treatment of mTBI and there is no consensus about management of these patients. 12 Therefor, variation in structure and process of mTBI care is expected, which may result in variation in outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In Europa ereignen sich jährlich 200 bis 300 Unfälle mit Hirnverletzungen pro 100 000 Einwohner 1 . Dabei zählen Stürze, Sportverletzungen und Auto- oder Fahrradunfälle zu den häufigsten Ursachen.…”
Section: Epidemiologie Und Klassifikation Von Schädel-hirn-traumataunclassified